Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Note: I am assuming the first equation is:
x+y = 3
Answer:
The solution to the system of equations is:
(x, y) = (-2, 36)
Therefore, the x-coordinate of the solution of the system
x = -2
Step-by-step explanation:
Given the system of equations
[tex]\begin{bmatrix}x+y=34\\ x-y=-38\end{bmatrix}[/tex]
subtracting the equations
[tex]x-y=-38[/tex]
[tex]-[/tex]
[tex]\underline{x+y=34}[/tex]
[tex]-2y=-72[/tex]
solve -2y for y
[tex]-2y=-72[/tex]
Divide both sides by -2
[tex]\frac{-2y}{-2}=\frac{-72}{-2}[/tex]
[tex]y=36[/tex]
For x+y=34 plug in y = 36
[tex]x+36=34[/tex]
Subtract 36 from both sides
[tex]x+36-36=34-36[/tex]
Simplify
[tex]x=-2[/tex]
Thus, the solution to the system of equations is:
(x, y) = (-2, 36)
Therefore, the x-coordinate of the solution of the system
x = -2
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.